2019
DOI: 10.1155/2019/9158016
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 Gene-Modified Human Amniotic Mesenchymal Stem Cells Augment Regenerative Wound Healing by Multiple Synergistic Effects

Abstract: Mesenchymal stem cells (MSCs) possess a capacity to enhance cutaneous wound healing that is well characterized. However, the therapeutic effect of MSCs appears to be limited. Modifying MSC target genes to increase necessary biological effects is a promising strategy for wound therapy. Interleukin-10 (IL-10) is an anti-inflammatory cytokine that has a therapeutic effect on wound healing. In this study, we modified human amniotic mesenchymal stem cells (hAMSCs) using recombinant lentiviral vectors for expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…IL-10 is a cytokine involved in the restoration of tissues via the regulation of in ammatory responses, extracellular matrix production, broblast functions, and angiogenesis [83,84]. Studies have shown that IFN-γ is a key player in activating the immunomodulatory function of murine and human MSCs through the production of several factors, including HGF and IL-10, which is consistent with the results of our study [85,86].…”
Section: Discussionsupporting
confidence: 90%
“…IL-10 is a cytokine involved in the restoration of tissues via the regulation of in ammatory responses, extracellular matrix production, broblast functions, and angiogenesis [83,84]. Studies have shown that IFN-γ is a key player in activating the immunomodulatory function of murine and human MSCs through the production of several factors, including HGF and IL-10, which is consistent with the results of our study [85,86].…”
Section: Discussionsupporting
confidence: 90%
“…We analyze the cytokine production of the pro-inflammatory chemokine IL-8 and IL-10 and TGF-β three isoforms in SCAPs. IL-10 is an important anti-inflammatory cytokine that plays a vital role in periodontal diseases, alters bone formation ( Zhang et al., 2014 ), and is able to regulate endothelial progenitor cell development in wound healing processes ( Xiao et al., 2019 ). IL-8 is an important chemokine of interest in periodontal diseases ( Finoti et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we analyzed the gene expression of IL10, MMP-2, GM-CSFF, and VEGFA in the process of cutaneous wound healing in a canine model treated with allogeneic ASCs. These gene products have important biological effects on wound healing [23,73].…”
Section: Discussionmentioning
confidence: 99%
“…However, for IL-10 and MMP-2 genes, there were no significant differences between treatments and between them; a possible explanation is that IL-10 regulates MMP-2 expression [73,78].…”
Section: Discussionmentioning
confidence: 99%